Development of canned meatballs from carabeef (Bubalus bubalis Linn.) Tita R. Agravante ; Belen O. Rillo, adviser. - Agravante, Tita Raposa (1975)
Development of canned meatballs from carabeef was undertaken in this study. Standardization of the formulation and process schedule and comparative study of its general acceptability were performed. Results of the first phase of the study showed that 10% all-purpose flour was the best binder to use. An adequate process schedule was established by trying out three time-temperature combinations namely, 40 minutes at 250°F, 50 minutes at 250°F, and 60 minutes at 250°F. Based on heat penetration studies, physico-chemical and cut-out tests, microbiological tests, and sensory evaluation of the canned products, processing schedule of 60 minutes at 250°F was selected as the best schedule among the three combinations studied. General acceptability of 100% carabeef meatballs was conducted by comparing it with meatballs made from combinations of different beef-carabeef proportions. A control group made up of 100% beef meatballs was prepared. Analyses of the sensory evaluation showed that 100% carabeef meatballs compare favorably with meatballs made up of beef-carabeef combinatio